Recession Defects Associated With Scraped Roots Treated With Subepithelial Connective Tissue Graft - Martins, Thiago Marchi [UNESP]; Bosco, Álvaro Francisco [UNESP]; Garcia, Valdir Gouveia [UNESP]; Nagata, Maria José Hitomi [UNESP]; Fernandes, Leandro Araujo [UNESP]; Murakawa, Ana Cristina [UNESP]; Ervolino, Edilson [UNESP] (Lippincott Williams & Wilkins, 2011)
The objective of the current study was to assess histo-morphometrically the healing process of recession defects associated with scraped roots treated with subepithelial connective tissue graft (SCTG). Six dogs were used. Bone dehiscence defects (6 x 8 mm) and root planing were carried out on maxillary canine teeth. Following a split-mouth model, according to the treatment, left canines (control) were covered with coronally positioned flap (CPF). Right canines were submitted to treatments with SCTG. After a 3-month postoperative period, the animals were killed, and the blocks processed for the histomorphometric assessment. Data assessment demonstrated that the CPF group showed parameters of a new connective tissue attachment, length of new cement (NC), length of new bone (mean +/- SD: 0.95 +/- 0.53, 2.44 +/- 1.97, and 1.96 +/- 2.29 mm, respectively), which were higher than those of SCTG group (mean +/- SD: 0.71 +/- 0.36, 2.21 +/- 1.28, and 1.52 +/- 1.31 mm, respectively), although not significantly (P > 0.05). The length of both epithelial tissue and connective tissue apposition in the SCTG group (mean +/- SD: 1.70 +/- 0.53 and 2.62 +/- 1.52 mm, respectively) were higher than those of the CPF group (mean +/- SD: 1.18 +/- 0.49 and 2.03 +/- 1.03 mm, respectively), although showing no significant differences (P > 0.05). Within the limits of the current study, it was possible to conclude that there were no significant differences between the groups according to the histologic parameters assessed.
Keywords: Wound healing; connective tissue; transplantation; animal models